THE DEVELOPMENT OF A HISTORY E-BOOK ON THE TOPIC OF THE ARRIVAL AND SPREAD OF ISLAM IN INDONESIA BASED ON LOCAL HISTORY (ROKAN ROYAL PALACE) TO IMPROVE LEARNING OUTCOMES OF GRADE X STUDENTS AT SMAN 1 UJUNGBATU: Pengembangan E-Book Sejarah Materi Masuk Dan Berkembangnya Islam di Indonesia Berbasis Sejarah Lokal (Istana Raja Rokan) Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas Kelas X Sman 1 Ujungbatu - Meisy Salsa Bella; Isjoni; Asril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Development of an e-book on the history of the entry and development of Islam in Indonesia based on local history (Istana Raja Rokan) using the ADDIE model. The first stage is needs analysis by identifying the needs, goals, knowledge and attitudes of students. This analysis stage is carried out by the author to collect the data needed in the development of this e-book. The second stage is design at this stage the author creates an e-book, in the design stage a conceptual framework for e-book development has been prepared. The third stage is development at this phase involves developing activities, creating goals, and contextual learning. In this development stage there are three activities that the author does, namely product creation, validation, and product revision. The fourth stage is implementation at this stage, namely applying the e-book design that has been developed to real situations in the classroom. The fifth stage is evaluation at this stage an evaluation is carried out to see suggestions and comments from the questionnaire assessment, this is done again so that this history e-book is truly in accordance with the needs and learning objectives. Based on the calculation results, it can be concluded that the development of this history e-book is